Govorna zmožnost dvojezičnih otrok v slovenskem jeziku - Hacin Beyazoglu, Kaja (Psihološka obzorja (Ljubljana), 2025)
The aim of this pilot study was to conduct a comparative analysis of the language abilities of monolingual and bilingual children in the Slovenian language and to examine the influence of family environment factors on various aspects of language development in both groups. The sample included 307 children aged 30 to 48 months: 262 monolingual children who were regularly exposed only to Slovenian at home, and 45 bilingual children who had been exposed daily and from birth to both Slovenian and an additional language in their home environment. The children’s language abilities were assessed using the Slovenian version of the CDI-III, focusing on vocabulary, grammar, and metalinguistic awareness. The results showed that monolingual children scored significantly higher than their bilingual peers in vocabulary and grammar when only one language was assessed, but not in metalinguistic awareness. Additionally, we found that family factors—such as the number of books at home, frequency of shared reading, the child’s age at the onset of shared reading, and parents’ education levels—were significantly associated with various domains of language development in Slovenian for monolingual children, but not for bilingual children. The findings of this pilot study highlight specific differences in the Slovenian language abilities of monolingual and bilingual children, underscore the importance of assessing bilingual children’s skills in both languages, and provide a basis for further research on bilingual language development in the Slovenian context.
Keywords: besednjak; bilingualism; children; družinska pismenost; dvojezičnost; family literacy; grammar; Lista sporazumevalnih zmožnosti za otroke CDI-III; Mcarthur-Bates communicative development inventory CDI-III; metajezikovno zavedanje; metalinguistic awareness; otroci; razvoj govora; slovnica; speech development; vocabulary